2012
DOI: 10.1681/asn.2012020137
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Parenchymal CD47 Promotes Renal Ischemia-Reperfusion Injury

Abstract: Ischemia-reperfusion injury (IRI) contributes to decreased allograft function and allograft rejection in transplanted kidneys. Thrombospondin-1 is a stress protein typically secreted in response to hypoxia and the ligand activator for the ubiquitously expressed receptor CD47. The function of activated CD47 in IRI remains completely unknown. Here, we found that both CD47 and its ligand thrombospondin-1 were upregulated after renal IRI in mice. CD47-knockout mice were protected against renal dysfunction and tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 44 publications
11
97
0
1
Order By: Relevance
“…3,15 To determine whether TSP1 is capable of stimulating O 2 z2 production in VSMC via activation of SIRP-a, we used a specific small interfering RNA (siRNA) (oligo 3) to suppress SIRP-a, then treated cells with TSP1 (2.2 nmol/L for 60 minutes) Figure 2. TSP1-stimulated phosphorylation of VSMC SIRP-a may not depend completely on CD47 activation.…”
Section: Tsp1 Activation Of Sirp-a Does Notmentioning
confidence: 99%
See 2 more Smart Citations
“…3,15 To determine whether TSP1 is capable of stimulating O 2 z2 production in VSMC via activation of SIRP-a, we used a specific small interfering RNA (siRNA) (oligo 3) to suppress SIRP-a, then treated cells with TSP1 (2.2 nmol/L for 60 minutes) Figure 2. TSP1-stimulated phosphorylation of VSMC SIRP-a may not depend completely on CD47 activation.…”
Section: Tsp1 Activation Of Sirp-a Does Notmentioning
confidence: 99%
“…3 To determine whether TSP1-SIRP-a-mediated stimulation of O 2 z2 is a general finding and extends to other parenchymal cells, we treated human rTECs with TSP1. Human rTECs expressed SIRP-a and SHP1 ( Figure 6, A and B), and TSP1 (2.2 nmol/L) treatment promoted rapid phosphorylation of SIRP-a and SHP1 ( Figure 6C) concurrent with stimulating increased O 2 z2 production ( Figure 6D).…”
Section: ·2mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, multiple studies have reported TSP1 induction under hypoxia (11,123,185,187) and in response to ischemia (52,219,241,260) or ischemia-reperfusion injuries (89,125,138,215,217,228,271), situations well known to upregulate ROS. This raises the intriguing hypothesis that ROS signaling may increase TSP1 expression.…”
Section: Tsp1 and Ros Signaling In Vivomentioning
confidence: 99%
“…Après ischémie-reperfusion [27], réduction néphronique [28], obstruction urétérale unilatérale [29], mais aussi au cours du vieillissement rénal [30], du diabète [31] et de nombreuses autres néphropathies glomérulaires expérimentales [32,33], les cellules épithéliales tubulaires expriment de novo la TSP-1. In vitro, l'hypoxie [34] et l'enrichissement du milieu de culture en glucose [31,35] [33]. Chez le rat, l'obstruction urétérale unilatérale induit une expression de novo de l'ARNm de tsp-1 et de la protéine TSP-1 par les tubules lésés.…”
Section: Expression De La Thrombospondine-1 Au Cours Des Néphropathieunclassified